Revisiting "The Power of Feedback" from the perspective of the learner. (April 2023) - Mandouit, Luke; Hattie, John
Highlights: Student perceptions provide unique insights into the literature relating to feedback. Different feedback types to have varying effects on learning, motivation, and emotions. The interplay between these variables will dictate to what level feedback is received and actioned. Feedback must answer What is done well? Where to improve? How to improve? and What to do next time?